2021
DOI: 10.3390/md19060293
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina Microalgae and Brain Health: A Scoping Review of Experimental and Clinical Evidence

Abstract: Spirulina microalgae contain a plethora of nutrient and non-nutrient molecules providing brain health benefits. Numerous in vivo evidence has provided support for the brain health potential of spirulina, highlighting antioxidant, anti-inflammatory, and neuroprotective mechanisms. Preliminary clinical studies have also suggested that spirulina can help to reduce mental fatigue, protect the vascular wall of brain vessels from endothelial damage and regulate internal pressure, thus contributing to the prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 74 publications
0
27
0
1
Order By: Relevance
“…The beneficial effects of Spirulina on the Central Nervous System (CNS) are also derived from the interaction between the Spirulina phytocomplex and the intestinal microbiota; there is a close relationship between the nervous system and the bowel, the bowel–brain axis [ 103 ]. The microbiota can transform Spirulina into antioxidant and micronutrient molecules that are able to cross the blood–brain barrier and express their beneficial effects such as the increase in energy production and the reduction of mental fatigue with the enhancement of learning skills; the synthesis of neurotransmitters (dopamine, serotonin, glycine, glutamate/GABA); an overall improvement in cognitive functions and short- and long-term memory [ 104 ]. On the other hand, Spirulina can increase the growth of protective bacteria in the bowel, thus maintaining a good balance and intestinal integrity and reducing systemic inflammatory responses that have a negative impact on the nervous system [ 105 , 106 ].…”
Section: Applications In Central and Peripheral Nervous Systemmentioning
confidence: 99%
“…The beneficial effects of Spirulina on the Central Nervous System (CNS) are also derived from the interaction between the Spirulina phytocomplex and the intestinal microbiota; there is a close relationship between the nervous system and the bowel, the bowel–brain axis [ 103 ]. The microbiota can transform Spirulina into antioxidant and micronutrient molecules that are able to cross the blood–brain barrier and express their beneficial effects such as the increase in energy production and the reduction of mental fatigue with the enhancement of learning skills; the synthesis of neurotransmitters (dopamine, serotonin, glycine, glutamate/GABA); an overall improvement in cognitive functions and short- and long-term memory [ 104 ]. On the other hand, Spirulina can increase the growth of protective bacteria in the bowel, thus maintaining a good balance and intestinal integrity and reducing systemic inflammatory responses that have a negative impact on the nervous system [ 105 , 106 ].…”
Section: Applications In Central and Peripheral Nervous Systemmentioning
confidence: 99%
“…However, less data exist on microalgae biomass being beneficial for sleep, mood and mental health. Nonetheless, Arthrospira platensis (originally known as Spirulina ) and Chlorella have been shown effective in neuroprotection, as they can protect against oxidative damage and inflammation [ 29 , 30 ]. Moreover, A. platensis was found to slightly decrease mental fatigue and improve cognitive function in clinical trials (3 g/day for seven days) [ 29 ].…”
Section: Therapeutic Potential Of Microalgae In Sleep and Mood Regula...mentioning
confidence: 99%
“…Nonetheless, Arthrospira platensis (originally known as Spirulina ) and Chlorella have been shown effective in neuroprotection, as they can protect against oxidative damage and inflammation [ 29 , 30 ]. Moreover, A. platensis was found to slightly decrease mental fatigue and improve cognitive function in clinical trials (3 g/day for seven days) [ 29 ]. Interestingly, Chlamydomonas reinhardtii cultures were found to generate a significant oxygen supply in the Central Nervous System (CNS) in situ.…”
Section: Therapeutic Potential Of Microalgae In Sleep and Mood Regula...mentioning
confidence: 99%
“…In animals, the fucoxanthin treatment enhanced the nuclear translocation of Nrf-2, which increases the expression levels of the HO-1 gene. This significantly improves the neurological functions, reduces infarction sizes, and decreases levels of proteins that are related to apoptosis in the brain [ 88 , 89 ]. Paudel et al, reported that fucoxanthin acted as an agonist for the activation of dopamine D3 and D4 receptors.…”
Section: Neuroprotective Effectmentioning
confidence: 99%